Pengaruh Penggunaan Jasa Endorse Dan Promosi Media Sosial Terhadap Keputusan Pembelian (Studi Kasus Pada Konsumen Kopi Tuwo Joyogrand Malang) - M Naufal Luthfi Azis; Agus Widarko; Muhammad Ridwan Basalama (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACT This research was conducted at Tuwo Coffee. This type of research is explanatory research with a quantitative approach. The purpose of this study was to determine the effect of using endorsement services and social media promotion on purchasing decisions. The independent variable used is the use of endorsement services and social media promotion, while the dependent variable is the purchase decision. The sample used in this study were 80 respondents who were consumers of Tuwo coffee. The data collection technique used a questionnaire. The analysis method used is the instrument test, normality test, multiple linear regression analysis, classical assumption test, determination test, F test and t test with the help of data processing computer software SPSS 16.0. The results of this study indicate that the use of endorsement services has an effect on purchasing decisions and social media promotion has an effect on purchasing decisions. The use of endorsement services and social media promotion simultaneously influences purchasing decisions.Keywords : Endorsement Services, Social Media Promotion, Purchasing Decisions.